Engineering turbulence modelling and experiments 4 : proceedings of the 4th International Symposium on Engineering Turbulence Modelling and Measurements, Ajaccio, Corsica, France, 24-26 May, 1999 /: proceedings of the 4th International Symposium on Engineering Turbulence Modelling and Measurements, Ajaccio, Corsica, France, 24-26 May, 1999. (1999) - Unknown
No abstract available